A nanocarrier pesticide delivery system with promising benefits in the case of dinotefuran: strikingly enhanced bioactivity and reduced pesticide residue. Issue 3 (28th January 2022) - Jiang, Qinhong; Xie, Yonghui; Peng, Min; Wang, Zhijiang; Li, Tianjiao; Yin, Meizhen; Shen, Jie; Yan, Shuo
Abstract : SPc can be conjugated with dinotefuran through hydrogen bonding and van der Waals forces, which reduce particle size, increase plant uptake and bioactivity, and decrease residue. The dinotefuran/SPc complex is relatively safe to predators and plants. Abstract : There is a growing demand for reducing pesticide application to minimize their potential threats to food/environmental safety. Herein, a star polymer (SPc) with low production cost was synthesized using two reactions, and it could be applied as an efficient pesticide nanocarrier/adjuvant. SPc could be spontaneously conjugated with dinotefuran through hydrogen bonding and van der Waals forces with a pesticide loading content (PLC) of 17.41%. The complexation of dinotefuran with SPc reduced the dinotefuran size from 269.28 to 29.43 nm and significantly decreased the contact angle of pesticide droplets from 53.4 to 27.9 degrees on plant leaves. The plant uptake of SPc-delivered dinotefuran was increased by 1.45 and 1.53 times those of dinotefuran alone at 6 and 12 h after treatment. As envisioned, in the dose-dependent experiments, the corrected mortality of aphids treated with the dinotefuran/SPc complex was finally increased by 18.4% (100 mg L −1 ), 15.0% (50 mg L −1 ) and 10.7% (25 mg L −1 ) compared to dinotefuran alone. Interestingly, the residue of dinotefuran delivered by SPc was decreased to 1.21, 1.37 and 2.30 times 3, 5 and 7 d after the treatment, respectively. Meanwhile, the dinotefuran/SPc complex showed no negative effects on agronomic traits (fresh weight, plant height, and leaf length and width) of oilseed rape; however it had a slight synergistic effect on non-target lady beetles due to the enhancement of broad-spectrum bioactivity. SPc is a promising pesticide adjuvant to improve the bioactivity of synthetic pesticides and decrease the pesticide residue, showing great potential for green pest management.